PROPHETIC LEADERSHIP MODEL IN ISLAM: A TRANSFORMATIONAL STRATEGY TO BUILD A POSITIVE ORGANIZATIONAL CULTURE IN EDUCATIONAL INSTITUTIONS - Rahman, Habibur; Tharaba, M. Fahim; Nasith, Ali (STKIP Pesisir Selatan, 2026)
Prophetic leadership is a holistic, transformational approach based on Islamic values, integrating spiritual, ethical, and practical dimensions into organizational management. This study aims to explore the implementation of the prophetic values of shiddiq, amanah, tabligh, and fathonah in building a positive organizational culture in Islamic educational institutions through a literature review analyzing classical and contemporary literature. The results of the study indicate that the application of the principles of monotheism, justice, deliberation, and amar ma'ruf nahi munkar not only strengthens the moral dimension of leadership but also enhances the coherence of values and behavior within the organization. These values play a strategic role in creating a harmonious, just, transparent, and morally sustainable culture, while simultaneously encouraging the formation of an educational environment that prioritizes the development of superior character, integrity, and noble morals. However, the effectiveness of the prophetic leadership model depends heavily on the leader's consistency, the organization's structural readiness, and a commitment to comprehensive value transformation. This study provides theoretical and practical contributions to the development of an Islamic-based educational leadership model relevant to the demands of the modern era. It also offers comprehensive insights for Islamic educational institution managers in designing leadership strategies capable of creating a more equitable, adaptive, and sustainable education system.